Organo-mineral fertilizers for sustainable agriculture - Katarzyna Chojnacka; Jonas Baltrusaitis (Sustainability Science and Technology)
Organo-mineral fertilizers (OMFs) combine organic and mineral components to enhance soil fertility, nutrient availability, and crop productivity while reducing environmental harm. They address key agricultural challenges, contributing to sustainable agriculture and global food security. OMFs utilize bio-based materials like biochar and compost to reduce nutrient leaching by up to 40%, improve water retention, and mitigate erosion. Improved soil aggregation, porosity, and microbial activity promote efficient nutrient cycling and resilience to environmental stress. Slow-release mechanisms optimize nutrient delivery, minimizing runoff and volatilization. OMFs increase soil organic carbon, support beneficial microbial communities, and enable sustainable intensification in nutrient-poor soils. They reduce greenhouse gas emissions, aligning with climate action goals and the United Nations Sustainable Development Goals. Precise nutrient management reduces input costs, improves yields, and reduces chemical residues in crops. OMFs contribute to the circular bioeconomy by transforming agricultural residues into nutrient-rich fertilizers, reducing waste by 20% and sequestering carbon to mitigate environmental degradation. Adoption challenges include optimizing formulations for diverse soils and efficiently scaling production. OMFs enhance sustainable agriculture by increasing crop yields, reducing greenhouse gas emissions by up to 30%, and mitigating nutrient leaching, supporting global goals for food security and climate change adaptation. Collaboration among researchers, policymakers, and agricultural stakeholders is essential for refining technologies and ensuring broader adoption.